The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3389/fncir.2012.00075
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of spectral and temporal integration in the mustached bat inferior colliculus

Abstract: This review describes mechanisms and circuitry underlying combination-sensitive response properties in the auditory brainstem and midbrain. Combination-sensitive neurons, performing a type of auditory spectro-temporal integration, respond to specific, properly timed combinations of spectral elements in vocal signals and other acoustic stimuli. While these neurons are known to occur in the auditory forebrain of many vertebrate species, the work described here establishes their origin in the auditory brainstem a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 128 publications
(261 reference statements)
1
31
0
Order By: Relevance
“…7). This timing result is in accordance with previous studies showing that pulse-evoked inhibition controls the latency of delay-tuned responses 25 . In all three species, the neuronal latency measured at the CD-MT point of the DRF was weakly correlated with the CD (that is, R ¼ 0.4 (P. quadridens and P. parnellii) and R ¼ 0.5 (C. perspicillata); see Supplementary Fig.…”
Section: Resultssupporting
confidence: 82%
“…7). This timing result is in accordance with previous studies showing that pulse-evoked inhibition controls the latency of delay-tuned responses 25 . In all three species, the neuronal latency measured at the CD-MT point of the DRF was weakly correlated with the CD (that is, R ¼ 0.4 (P. quadridens and P. parnellii) and R ¼ 0.5 (C. perspicillata); see Supplementary Fig.…”
Section: Resultssupporting
confidence: 82%
“…Such neurons exhibit either excitatory or inhibitory responses when two tones with distinctly different frequencies are presented simultaneously. It has been shown that facilitatory and inhibitory combination sensitivity originate in the IC and LL, respectively , with inhibition mechanisms and glycinergic inputs playing critical roles in creating such responses Wenstrup, 2005, 2006;Wenstrup et al, 2012). Previous electrophysiological studies also reported similar percentage of facilitatory and inhibitory combination-sensitive neurons.…”
Section: Uhf Encoding In the Icmentioning
confidence: 81%
“…Based on electrophysiological studies, they should also operate for combinations of an UHF and a lower frequency (Portfors and Felix, 2005;Portfors and Roberts, 2014;Portfors et al, 2009;Wenstrup et al, 2012). Such combinations were not examined in the present study, because a lower frequency itself would be expected to evoke BOLD responses, which would confound the combination-or distortion-evoked responses.…”
Section: Choices Of Frequencies In the Two-tone Paradigmmentioning
confidence: 93%
See 1 more Smart Citation
“…The smaller the echo-delay the shorter the distance to an object. Within the ascending auditory pathway, neurons whose response is facilitated when presented with specific echo-delays can be found as early as in the auditory midbrain11 and these neurons are defined as target-distance or delay-tuned neurons.…”
mentioning
confidence: 99%